Sustainable Village Waste Operations in Muncar, Indonesia: Community Management and Economic Impact Lessons for Indonesia and Beyond - Toat, Akhmad Prasetyo Ibnu; Kartikaningsih, Hartati; Atikawati, Dini (Postgraduate School of Universitas Brawijaya, 2025)
Waste management in Muncar, Banyuwangi, East Java, faces critical challenges, with 40 tons of waste generated daily and only 11% of the population accessing waste collection services by 2018. PROJECT STOP was introduced to address these issues through an integrated waste management strategy that combines governance, facility development, behavior change initiatives, and partnerships with local government. This study used a variety of methods, such as collecting data on waste production, judging the effectiveness of waste processing facilities, and polling people in the community to find out what role institutional frameworks like village-owned businesses (BUMDes) and community-based organizations (KSM) play in promoting sustainable waste governance. The results showed that PROJECT STOP used two types of governance models: the Village Waste Operator Model, which cut costs by 29% (from USD 31.2 to USD 22.2 per ton) by getting people to work together, and the Joint Village Model, which centralized operations across five villages and kept costs at USD 25 per ton while making them more efficient. Collectively, the initiative managed 16,876 tons of waste, served 90,773 residents, and improved operational efficiency through resource sharing and institutional support. The lessons learned from PROJECT STOP show how important collaborative governance is for building waste management systems that are both long-lasting and scalable. Additionally, they offer a model for addressing issues comparable to those in other regions of Indonesia. Keywords: waste management, collaborative, community waste governance, institutional framework